Health Risk Behaviors: Smoking, Alcohol, Drugs, and Dating among Youths in Rural Central Java - Shaluhiyah, Zahroh; Musthofa, Syamsulhuda Budi; Indraswari, Ratih; Kusumawati, Aditya (UI Scholars Hub, 2020)
Adolescents are more likely to adopt risky health behaviors, such as smoking, alcohol use, and sexual activity. This study examined the links betweensmoking, alcohol use, and risky dating behavior and analyzed how these factors influenced risky dating and other behaviors. It is expected that this studywould be used as a foundation for developing appropriate integrated intervention for multiple risk behaviors among youths. This study was an explanatory research study with a cross-sectional approach. It involved 160 youths aged 15-24 years randomly selected from purposive villages. Participants completedself-administrated questionnaires with an enumerator present. Data were analyzed using univariate, chi-square, and multiple logistic regression. Smoking behavior, leisure activity, and self-efficacy were predictors of risky dating behavior. The self-efficacy variable also influenced multiple risk behaviors. A strong association was found between smoking, risky dating behavior, and alcohol use. One-third of the participants had dated and smoked recently, but only 10% ofthem had experienced high-risk dating activity, including petting and intercourse. Only 5% had experienced alcohol use (in particular, traditional alcohol), andno one admitted being involved with drug abuse.